An Exploration of Problem-Solving Style through the lens of Psychological Climate, Cognitive Style and Idea Style Measures - Clapp, Ray; Rucktum, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
There is a growing interest in a more inclusive conception of the activity of the ‘change process’ (person, product, process and press) particularly the aspects of the creative sub-process concerned with person and product. The variables Cognitive style and Idea style, have a common heritage that is rooted in a dichotomy concerned at one end with ‘adaption’ (improvements) while at the other end with ‘innovation’ (novelty). These characteristics have been used to describe the ‘creative concept’ where to date the emphasis has been on the pole concerned with ‘innovation continuum’. The pole is hence also concerned with adaption, but while the pole being a necessary and central aspect of both variables has nevertheless received relatively little attention. In this study, the primary objective was therefore to evaluate the coherence of Kirton’s ‘cognitive style’ measure of adaptive – innovative behavioural preferences with the measures of Idea styles. Therefore, another related objective was to evaluate the relationship between the cognitive style and ‘psychological climate’, consisting of ideas generated and problems identified as sub-components. The results show the ‘innovative pole’ of cognitive style is significantly related to both innovative idea style and the quantity of ideas generated (it is also explicitly supported by the facets of the personality variable ‘openness’). However, while a negative relationship between cognitive style and the adaptive style of ideas is a central aspect of Kirton’s cognitive style theory, no significant negative relationship was found. Instead, the adaptive style of ideas has a positive relationship to a factor within the measure of psychological climate or ‘the opportunity to contribute to change’. These findings position Kirton’s cognitive style measure as primarily in the domain of ‘personality’ and only partially coherent with the domain of ‘idea style’ the latter a carrier, rather than ‘a component of style’. Furthermore, while the variables of cognitive style and psychological climate show no significant relationship, they provide differential support to the ‘first two stages’ of the change process.